Checklist of the Plecoptera of Brazilian Amazon (Insecta: Plecoptera: Perlidae) - Ribeiro, José Moacir Ferreira; Dos Santos, Cléverson Ranniéri Meira (Zootaxa, 2018)
The species diversity of the Plecoptera of the Brazilian Amazon is still little known, although some localities have been relatively well-studied. A preliminary list of 27 valid Plecoptera species, based on collections from 66 different localities is presented. Additional efforts to collect Plecoptera at new sites should considerably increase the number of recorded species of Amazonian.